Simulation and study of energy performance of membrane based dedicated outdoor air system (DOAS) in air-conditioning systems for hot and humid climate - Cho, Dee Fei (2014)
Presently, heating, ventilation and air conditioning (HVAC) accounts for roughly 50% of the total energy consumption in buildings such as offices and hotels (Pérez-Lombard, Ortiz et al. 2008) With the current emphasis on environmental awareness, several methods have been developed in an effort to reduce the energy consumed by the HVAC system. Besides saving energy, there is also a need for better Indoor Air Quality (IAQ), through controlling the level of humidity within the space, so as to prevent excess moisture buildup, which may create favourable conditions for bacteria and microbes to breed in. To tackle these issues, the concept of a Dedicated Outdoor Air System (DOAS) has been suggested by Mumma (Mumma 2001), . A previous study conducted by Teo (Teo 2013)assessed the feasibility of integrating DOAS with the current AHU systems in NTU’s lecture theatres, which has been found to save costs, but unsuitable for practical applications, due to the high flow rate of outdoor air required for the lecture theatres. Multiple DOAS units would be required, which would occupy a large floor area within a building space. This would result in increased ductings, as well as increased complexity in connecting the DOAS units together to provide a steady flow. Thus, the author aims investigate the feasibility of the DOAS when integrated with existing AHU system in NTU’s N3-2 offices. Software such as TRNSYS and Carrier’s Hourly Analysis Program will be used to simulate the DOAS. It was found that in addition to cost savings, lesser DOAS units were required, due to a lower rate of outdoor air flow required, contributing to space savings as well